Reading Life with Gwich'in - Laurens Loovers, Jan Peter. (Milton)
1 online resource (287 pages).
Keywords: This book is based upon more than two years of ethnographic fieldwork and personal experiences with the Teet'it Gwich'in community in northern Canada. The author provides insight into Gwich'in understandings of life as well as into historical and political processes that have taken place in the North. He outlines the development of an educational approach towards conducting ethnography and writing anthropological literature, starting with the premise you have to live it'. The book focuses on ways of knowing and collaboration through learning and being taught by interlocutors. Building on the work of Tim Ingold, Loovers investigates the notion of reading life - land, water and weather as well as texts - and analyses the reading of texts as acts of conversations or correspondences.